Anatomical Variations in the Location of Veins Draining Into the Anterior Superior Sagittal Sinus: Implications for the Transbasal Approach. Issue 6 (21st November 2019) - Borghei-Razavi, Hamid; Raghavan, Alankrita; Eguiluz-Melendez, Aldo; Joshi, Krishna; Fernandez-Miranda, Juan C; Kshettry, Varun R; Recinos, Pablo F
Abstract: BACKGROUND: Many approaches are used for midline anterior cranial fossa meningioma resection. In the subfrontal approach, the anterior superior sagittal sinus (SSS) is commonly ligated to release the anterior falx. The transbasal approach allows access to the origin of the anterior SSS, allowing for maximum venous preservation. OBJECTIVE: To investigate variations in the first and second veins draining into the SSS. METHODS: We performed stepwise dissections for a transbasal level 1 approach on 8 anatomic specimens. We visualized the first and second veins draining into the sinus and measured the distance from the foramen cecum to these veins. We also measured the orbital bar height to determine the length of sagittal sinus that could be preserved with orbital bar removal. RESULTS: The distance between the foramen cecum and the first vein ranged from 4 to 36 mm while the distance to the second vein ranged from 6 to 48 mm. The mean orbital bar height was 26.4 mm. Based on these measurements, with a traditional bicoronal craniotomy without orbital bar removal, 81% of first veins and 58% of second veins would be sacrificed. CONCLUSION: A supraorbital bar or nasofrontal osteotomy, part of the transbasal skull base approach, is helpful to preserve the first and second veins when ligating the anterior SSS. Based on this study, it may be difficult to preserve these veins without orbital bar removal. Preservation of these veins may be of clinical importance when approaching midline anterior fossa pathologies.